Analisis Risiko Produksi dan Pendapatan Usahatani Ubi Jalar di Kabupaten Kuningan - Millah, Rio Fauzi Saeful; Rochdiani, Dini; Qianti, Sara Ratna (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Sweet potatoes are a very important agricultural commodity and play a role in ensuring food security and increasing farmers' income. However, many farmers in the region still face difficulties in maximizing their production and income, in addition to facing various risks that can affect their agricultural yields. This study aims to assess the level of risk faced by farmers in the sweet potato cultivation business, both in terms of production and income, as well as to identify mitigation efforts carried out by farmers in reducing these risks. This study uses a quantitative descriptive method involving 100 respondents from sweet potato farmers in Cilimus District, Kuningan Regency, which were selected through a proportional random sampling technique. The results showed that the average sweet potato production by farmers was 9,472.50 kg per 0.43 hectares, with an average income of Rp7,888,653.56 per 0.43 hectares per planting season. Production risk analysis revealed a coefficient of variation of 1.00, with the lower limit of production reaching Rp -9,548.91 kg. Meanwhile, the coefficient of variation in revenue was recorded at 0.93, with the lower limit of income of Rp -6,632,997.55 per 0.43. From these results, it is known that the risks faced by sweet potato farmers in Kuningan Regency are relatively high, both in terms of production and income.